Active methodologies in the socio-educational pedagogical process (Research, Society and Development, 2022)
Understanding and assimilating the rules of coexistence are the basic definitions for the social being, linked to a process of socialization, and at the other end of this process are juvenile offenders who, after completing their socio-educational measure, go in search of their resocialization as provided for in the National Socio-Educational System (SINASE), as a final procedure for their educational and training internment, being ready for social insertion and replacement in the labor market as well as following their education, fulfilling the provisions of the Child and Adolescent (ECA). A resocialization based on continuing education, on the use of active methodologies, which are increasingly focused on the student's previous knowledge, on their experiences and experiences, which can contribute to the educational evolution and knowledge itself. This work is an integral part of the Master's thesis in Methodology and Teaching of Humanities and Languages ​​at the Franciscan University, which uses the socio-educational theme as an object of study and research, as well as its pedagogical practices and methodologies. In this way, the need to understand resocialization as an opportunity to change, replace or even maintain the social, cultural and educational status of adolescents admitted to a socio-educational care unit capable of inferring in the lives of these adolescents and in the insertion of these adolescents in the social life and their eventual reintegration.